Adoption of Scientific Poultry Farming Practices by the Farmers in Ajmer District of Rajasthan - Jat, S.M.; Yadav, J.P. (Indian Journal of Extension Education, 2012)
Poultry farming has proved that it can ensure economic and social rehabilitation of weaker sections of the society. The  knowledge and adoption of poultry farming are inter linked. It was observed that all the three categories of registered  farmers adopted the recommended poultry farming practices at higher extent in comparison to unregistered poultry  farmers. Although, a highly significant difference between different categories i.e. between the big and medium, big and  small, medium and small of registered and unregistered poultry farmers was observed about extent of adoption of the  recommended poultry farming practices. The study concludes that registered poultry farmers may have obtained training  and exposure which enhanced the knowledge and ultimately had to encourage the farmers for more adoption of  recommended poultry farming practices.
Keywords: Poultry; Knowledge; Adoption; Improved technology